The dismal state of macroeconomics and the opportunity for a new beginning - L. Randall Wray (Levy Economics Institute of Bard College, 2011)
The Queen of England famously asked her economic advisers why none of them had seen it (the global financial crisis) coming. Obviously, the answer is complex, but it must include reference to the evolution of macroeconomic theory over the postwar period - from the Age of Keynes through the Friedmanian era and the return of Neoclassical economics in a particularly extreme form, and, finally, on to the New Monetary Consensus, with a new version of fine-tuning. The story cannot leave out the parallel developments in finance theory - with its efficient markets hypothesis - and in approaches to regulation and supervision of financial institutions. This paper critically examines these developments and returns to the earlier Keynesian tradition to see what was left out of postwar macro. For example, the synthesis version of Keynes never incorporated true uncertainty or unknowledge and thus deviated substantially from Keynes's treatment of expectations in chapters 12 and 17 of the General Theory. It essentially reduced Keynes to sticky wages and prices, with nonneutral money only in the case of fooling. The stagflation of the 1970s ended the great debate between Keynesians and Monetarists in favor of Milton Friedman's rules, and set the stage for the rise of a succession of increasingly silly theories rooted in pre-Keynesian thought. As Lord Robert Skidelsky (Keynes's biographer) argues, Rarely in history can such powerful minds have devoted themselves to such strange ideas. By returning to Keynes, this paper attempts to provide a new direction forward.
Keywords: A2; B15; B22; B50; E11; E12; G01; 330; efficient markets hypothesis; Keynesian economics; orthodoxy; heterodox economics; Minsky; uncertainty; rational expectations; new classical; new monetary consensus; monetary theory of production; effective demand; special properties of money; the end of laissez-faire; financial instability hypothesis